Circulating Monocyte Subsets Are Associated With Extent of Myocardial Injury but Not With Type of Myocardial Infarction - Askari, Noushin; Lipps, Christoph; Voss, Sandra; Staubach, Nora; Grün, Dimitri; Klingenberg, Roland; von Jeinsen, Beatrice; Wolter, Jan Sebastian; Kriechbaum, Steffen; Dörr, Oliver; Nef, Holger; Liebetrau, Christoph; et al. (Frontiers in Cardiovascular Medicine, 2021)
Inflammation is a hallmark of the period after a myocardial infarction (MI) that is either promoted or resolved by distinct subtypes of circulating inflammatory cells. The three main monocyte subpopulations play different roles inflammation. This study examined whether the type of MI (type 1 or type 2) or the extent of myocardial injury is associated with differences in monocyte subpopulations. For this purpose, peripheral whole blood from patients with a suspected MI was used for flow cytometric measurements of the monocyte subpopulations, and myocardial injury was classified by cardiac troponin levels in serum. In patients with acute coronary syndrome (n=82, 62.2% male) similar proportions of the monocyte subsets were associated with the two types of MI, whereas total monocyte counts were increased in patients with substantial myocardial injury vs. those with minor injury (p=0.045). This was accompanied by a higher proportion of intermediate (p=0.045) and classical monocytes (p=0.059); no difference was found for non-classical monocytes (p=0.772). In patients with chronic coronary syndrome (n=144, 66.5% male), an independent association with myocardial injury was also observed for classical monocytes (p=0.01) and intermediate monocytes (p=0.08). In conclusion, changes in monocyte subpopulation counts, particularly for classical and intermediate monocytes, were related to the extent of myocardial injury in acute and stable coronary artery disease but not to the type of MI.